"This Is Not a Photograph of a Fetus": A Feminist Reconfiguration of the Concept of Posthumanism as the Ultrasoundfetusimage. (November 2017) - Taguchi, Hillevi Lenz
Inspired by Claire Colebrook and Deleuze and Guattari, I aim to make the concept of posthumanism itself my "method." The objective of such an inquiry is a growing self-critique of how posthumanism has, in part, been adopted in educational research. Concept as method puts the concept to play on, in this case, a feminist plane of thinking, to trace-and-map the problems and components from which the concept emerges; that is, it takes on its meanings and practices on this particular plane. Hereby, a reconfigured "face" of the concept of posthumanism takes the shape of the ultrasoundfetusimage .